2014
DOI: 10.5539/gjhs.v7n3p254
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Family Functioning and Mental Health Considering the Mediating Role of Resiliency in Type 2 Diabetes Mellitus Patients

Abstract: This study was aimed at describing the mediating role of resiliency in the relationship between family functioning and mental health in patients with type 2 diabetes mellitus. This descriptive research was a correlational study. A total of 225 individuals were chosen by simple random sampling technique from type 2 diabetic patients presented to diabetes care centers in Kermanshah in 2014 in Iran. The 12-item General Health Questionnaire (GHQ-12), the Family Assessment Device (FAD) and the Resilience Scale (CD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 13 publications
4
20
2
1
Order By: Relevance
“…As in previous studies (Pinquart, ; Bahremand et al, ), our results showed that higher levels of resilience are associated with higher levels of mental HRQoL. The relationship between resilience and mental health is very close.…”
Section: Discussionsupporting
confidence: 89%
“…As in previous studies (Pinquart, ; Bahremand et al, ), our results showed that higher levels of resilience are associated with higher levels of mental HRQoL. The relationship between resilience and mental health is very close.…”
Section: Discussionsupporting
confidence: 89%
“…These measures have also been clinically used as screeners for establishing treatment referrals in PHC settings and for disability claimants (Allen et al, ; Cornelius, Groothoff, van der Klink, & Brouwer, ; Donker et al, ; Fassaert et al, ; Furukawa, Kessler, Slade, & Andrews, ; Kessler et al, ). We further compared the psychometric properties of these measures with the 12‐item General Health Questionnaire (GHQ‐12) that has been validated and extensively used in Iran (Bahremand et al, ; Emami, Ghazinour, Rezaeishiraz, & Richter, ; Heidari, Feizi, Roohafza, Hassanzadeh Keshteli, & Adibi, ; Montazeri et al, ) and other countries (Danielsson, Lundin, Allebeck, & Agardh, ; Diniz et al, ; Padron, Galan, & Rodriguez‐Artalejo, ; Pope et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…53,54 Edwards and Clarke 53 have demonstrated that good family functioning was associated with lower levels of psychological distress, depression and anxiety. Bahremand et al 54 supposed that there was an indirect relationship between family functioning and mental health. Previous studies found that general well-being can mediate the relationship between other variables and mental health.…”
Section: Discussionmentioning
confidence: 99%